Galerie Michael Haas 2000. - Galerie Michael Haas, Berlin (Berlin : Galerie Michael Haas, 2000)
Amiet, Cuno ; Bess, Foresst ; Bonnard, Pierre ; Braque, Georges ; Chaissac, Gaston ; Corinth, Lovis ; Derain, André ; Dix, Otto ; Dubuffet, Jean ; Fautrier, Jean ; Gontcharova, Natalja ; Grosz, George ; Hodler, Ferdinand ; Hofer, Karl ; Leger, Fernand ; Marini, Marino ; Miro, Joan ; Mondriaan, Piet ; Picasso, Pablo ; De Smet, Gustave ; Soutter, Louis ; Vallotton, Félix
biografie
boek